Smartphone apps: A state-of-the-art approach for oral health education. - Prajna Nayak; Sushma Nayak; Vikneshan M; Shashidhar Acharya; Deepicca Sathiyabalan (Universidad de Concepción., 2019)
While there is an ever increasing use of smartphones in recent times, cellular phone based mobile applications (apps) are hardly used by the public to improve oral health. Hence, this cross-sectional study was conducted to evaluate the features of the current oral health education smart phone apps pertaining to dental patients. Materials and Methods: Oral health terms were queried in the online app stores. Among the apps found, all patient-related apps were listed and categorized. The apps were assessed for type, cost, rating, average number of downloads, involvement of dental professional in their development, target group, local or global applicability, the benefits and drawbacks of the apps and user reviews. Results: A total of 146 oral health apps for patient use were found, with the most common being about techniques for oral hygiene (33.5%) and tooth brushing timers (25.3%). The majority of apps (69.2%) were available for downloading for no cost. 'Happy teeth, healthy kids app', 'Disney Magic timer' and 'Happy Kids timer' were the most downloaded apps. Conclusion: A considerable number of mobile apps are currently available for patients to help them in maintaining oral health, though most of them are brushing timers or demonstrate oral hygiene techniques.